2021
DOI: 10.1101/2021.01.11.426186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YHP: Y-chromosome Haplogroup Predictor for predicting male lineages based on Y-STRs

Abstract: Human Y chromosome reflects the evolutionary process of males. Male lineage tracing by Y chromosome is of great use in evolutionary, forensic, and anthropological studies when male samples exist or especially when the biological sample is a mixture of male and female individuals. Identifying the male lineage based on the specific distribution of Y haplogroups narrows down the investigation scope. Integrating previously published datasets with genotypes of Y chromosome short tandem repeats (Y-STRs) and high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
(28 reference statements)
0
19
0
2
Order By: Relevance
“…With the same polymer backbone, mPPCs with 7% LD loading were better inhibitors than those with 3% or 12% loading. 10 We further reported that mPPCs at a constant 7% LD loading disassemble mature fibrils with a dependence on polymer MW. 11,12 However, it remains unclear 1) if the conjugation strategy is applicable to ligands other LD; 2) how the ligand loading and polymer MW affect mPPC inhibition potency in tandem; and 3) what the origin of such dependence is at the molecular level.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…With the same polymer backbone, mPPCs with 7% LD loading were better inhibitors than those with 3% or 12% loading. 10 We further reported that mPPCs at a constant 7% LD loading disassemble mature fibrils with a dependence on polymer MW. 11,12 However, it remains unclear 1) if the conjugation strategy is applicable to ligands other LD; 2) how the ligand loading and polymer MW affect mPPC inhibition potency in tandem; and 3) what the origin of such dependence is at the molecular level.…”
Section: Introductionmentioning
confidence: 81%
“…10 We further reported that mPPCs at a constant 7% LD loading disassemble mature fibrils with a dependence on polymer MW. 11,12 However, it remains unclear 1) if the conjugation strategy is applicable to ligands other LD; 2) how the ligand loading and polymer MW affect mPPC inhibition potency in tandem; and 3) what the origin of such dependence is at the molecular level. Here we report the preparation and inhibition properties of mPPCs of three different ligands, with systematic investigation of ligand loading and polymer MW.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies implicated QS-1 and, to a lesser extent, QS-3 of B. pseudomallei in animal infections. [11][12][13] The QS systems of B. mallei were also initially shown to contribute to virulence. 14 Although later results did not corroborate these initial findings, 15 the conservation of QS-1 and QS-3 in B. mallei supported the idea that these two systems play a role during survival in the host.…”
Section: Burkholderia Thailandensis Studies Prior To Collaborationmentioning
confidence: 99%
“…HR-MS analysis of the most abundant bactobolin variant, bactobolin A, was consistent with the presence of two chlorine substituents. Indeed, a singlet deshielded peak at 6.18 ppm, with a corresponding 74 ppm 13 C shift, was symptomatic of a methine-carbon carrying two chlorine substituents. The structure of bactobolin A was ultimately solved by analysis of a full suite of 1D/2D NMR spectra and shown to be identical to that previously solved by Kondo and co-workers (Figure 1b).…”
Section: Bactobolin Isolation and Characterizationmentioning
confidence: 99%